The acute effects intensity and volume of strength training on running performance - Doma, K.; Bede Deakin, G. (European Journal of Sport Science, 2014)
Strength training has been shown to cause acute detrimental effects on running performance. However, there is limited investigation on the effect of various strength training variables, whilst controlling eccentric contraction velocity, on running performance. The present study examined the effects of intensity and volume (i.e. whole body vs. lower body only) of strength training with slow eccentric contractions on running economy (RE) [i.e. below anaerobic threshold (AT)] and time-to-exhaustion (TTE) (i.e. above AT) 6 hours post. Fifteen trained and moderately endurance trained male runners undertook high-intensity whole body (HW), high-intensity lower body only (HL) and low-intensity whole body (LW) strength training sessions with slow eccentric contractions (i.e. 1:4 second concentric-to-eccentric contraction) in random order. Six hours following each strength training session, a RE test with TTE was conducted. The results showed that HW, HL and LW sessions had no effect on RE and that LW session had no effect on TTE (P?0.05). However, HW and HL sessions significantly reduced TTE (P<0.05). These findings demonstrate that a 6-hour recovery period following HW, HL and LW sessions may minimize attenuation in endurance training performance below AT, although caution should be taken for endurance training sessions above AT amongst trained and moderately endurance trained runners.